A Recurrent Mutation in Anaplastic Lymphoma Kinase with Distinct Neoepitope Conformations - Toor, Jugmohit S.; Rao, Arjun A.; McShan, Andrew C.; Yarmarkovich, Mark; Nerli, Santrupti; Yamaguchi, Karissa; Madejska, Ada A.; Nguyen, Son; Tripathi, Sarvind; Maris, John M.; Salama, Sofie R.; Haussler, David; et al. (Frontiers in Immunology, 2018)
ABSTRACT The identification of recurrent HLA neoepitopes driving T cell responses against tumors poses a significant bottleneck in the development of approaches for precision cancer therapeutics. Here, we employ a bioinformatics method, Prediction Of T Cell Epitopes for Cancer Therapy (ProTECT) to analyze sequencing data from neuroblastoma patients and identify a recurrent Anaplastic Lymphoma Kinase mutation (ALK R1275Q) that leads to two high affinity neoepitopes when expressed in complex with common HLA alleles. Analysis of the X-ray structures of the two peptides bound to HLA-B*15:01 reveals drastically different conformations with measurable changes in the stability of the protein complexes, while the self-epitope is excluded from binding due to steric hindrance in the MHC groove. To evaluate the range of HLA alleles that could display the ALK neoepitopes, we used structure-based Rosetta comparative modeling calculations which accurately predict several additional high affinity interactions, and compare our results with commonly used prediction tools. Subsequent determination of the X-ray structure of an HLA-A*01:01-bound neoepitope validates atomic features seen in our Rosetta models with respect to key residues relevant for MHC stability and T cell receptor recognition. Finally, MHC tetramer staining of peripheral blood mononuclear cells from HLA-matched donors shows that the two neoepitopes are recognized by CD8+ T cells. This work provides a rational approach towards high-throughput identification and further optimization of putative neoantigen/HLA targets with desired recognition features for cancer immunotherapy.